THE PERCEPTION OF PARENTS OF CHILDREN AND ADOLESCENTS WITH AUTISM ABOUT SCHOOL INCLUSION (Interdisciplinary Studies Journal, 2024)
Autism, according to medical conventions, is characterized as a neurodevelopmental disorder whose symptoms present in the spheres of language, behavior and socialization. Such a diagnosis changes family relationships, producing a work of mourning for the imagined child, outlining, by extension, the possible and impossible paths to schooling. This article investigates the perceptions of parents of children and adolescents with autisms regarding inclusion in Regular Education at a school in the Metropolitan Region of Porto Alegre/RS. Seven parents who had children enrolled in the educational institution participated in the study. Two instruments were used to collect data, namely: sociodemographic questionnaire and semi-structured interview guide. The interviews were recorded and transcribed in full. Afterwards, the theoretical corpus was analyzed based on the assumptions of Bardin's Content Analysis, with the help of the MAXQDA software. As a theoretical framework, assumptions originating from psychoanalytic studies in dialogue with education were adopted. The results indicated emotional impacts on parents in situations of social exclusion, greatly affecting their interaction with the social environment. On the other hand, it pointed out that school is an important space for students’ socio-emotional development and support in their paths to be crossed.
Keywords: Autism; School Inclusion; Parents; TEA